STRENGTHENING UMKM BUSINESS â€œMADU YBSâ€ THROUGH BUSINESS MANAGEMENT ASSISTANCE AND FACILITATION OF PRODUCT LEGALITY DOCUMENTS - Yudha, I Made Endra Kartika; Haryanti, Ni Putu Premierita; Suhartika, I Putu; Suasih, Ni Nyoman Reni (Jurnal Abdi Insani, 2022)
UMKM Honey YBS is a micro business that sells honey products. Honey products sold by YBS Honey SMEs have been marketed to several restaurants, but due to the COVID-19 pandemic, the demand for these honey products has decreased drastically. This community service aims to provide solutions to problems in business management aspects related to permits, financial reports, and target markets. The implementation method consists of identification of needs, assistance, facilitation of licensing processes, mentoring and evaluation. The main internal problem faced by MSME Madu YBS is in the business aspect and product legality. The product has a relatively low selling value compared to similar MSME products because it does not have a product license. Unbalanced product needs and supply become the basis for business assistance in order to find other sources of raw materials. For this reason, the activity implementation team conducted a field survey to find new sources of raw materials from different suppliers. The survey results show that there are potential new suppliers in Payangan District, Gianyar Regency, which consist of home-based honey bee farmer groups. In the third phase of activities, partners are provided with assistance in managing the Food-Household Industry (P-IRT) licensing. The fourth stage of activity is carried out by assisting in the preparation of simple financial reports in the form of general ledger, cash flow, stock, and accounts receivable reports. As an effort to evaluate activities, the service team directly or indirectly (through student field staff) communicates with MSME owners if in the early stages of implementing the assistance results there are still problems. Assistance activities result in identification of existing suppliers, production targets, legality permits for products, and simple financial statements.